A Low‐Voltage Microfluidic Valve Based upon a Reversible Hydrophobicity Effect. Issue 16 (27th May 2016) - Wang, Ran; Yu, Weijie; Kozicki, Michael N.; Chae, Junseok
Abstract : A microfluidic valve is reported based on a reversible hydrophobicity effect via the growth and retraction of nanotextured metal filaments on the surface of a solid electrolyte. The valve is integrated onto the bottom of the channel and actuated by a DC voltage. The dendritic silver filaments are tens to hundreds of nanometers in height and can be isolated from the channel fluid by a thin Parylene layer. An applied bias of 6 V or less grows or dissolves the filaments, depending on the polarity, and the roughness so created alters the fluid‐surface interface, manipulating hydrophobicity of the interface, transitioning from the lotus effect to the petal effect. To demonstrate this valve, the fluid flow in a poly(dimethylsiloxane)‐enclosed microfluidic channel of up to 30 μm in depth and up to 250 μm in width is stopped and restarted within ≈25 s of actuation. The effect is nonvolatile, thus no static power is required to retain the on/off states of the valve. Abstract : The nanoscale valving based on roughness manipulation is enabled by growing and retracting the dendritic silver filaments on chalcogenide solid electrolyte surfaces. The optical profilometry and scanning electron microscopy images show the surface roughness and morphology. The nanoscale filaments grow under a thin Parylene film. On/off valve operation and the measured flow rate correspond to the DC power supply.